Molecular basis for azetidine-2-carboxylic acid biosynthesis - Tim J. Klaubert; Jonas Gellner; Charles Bernard; Juliana Effert; Carine Lombard; Ville R. I. Kaila; Helge B. Bode; Yanyan Li; Michael Groll (Nature Communications)
Abstract Azetidine-2-carboxylic acid (AZE) is a long-known plant metabolite. Recently, AZE synthases have been identified in bacterial natural product pathways involving non-ribosomal peptide synthetases. AZE synthases catalyse the intramolecular 4-exo-tet cyclisation of S-adenosylmethionine (SAM), yielding a highly strained heterocycle. Here, we combine structural and biochemical analyses with quantum mechanical calculations and mutagenesis studies to reveal catalytic insights into AZE synthases. The cyclisation of SAM is facilitated by an exceptional substrate conformation and supported by desolvation effects as well as cation-π interactions. In addition, we uncover related SAM lyases in diverse bacterial phyla, suggesting a wider prevalence of AZE-containing metabolites than previously expected. To explore the potential of AZE as a proline mimic in combinatorial biosynthesis, we introduce an AZE synthase into the pyrrolizixenamide pathway and thereby engineer analogues of azabicyclenes. Taken together, our findings provide a molecular framework to understand and exploit SAM-dependent cyclisation reactions.